2017
DOI: 10.1109/tip.2017.2716843
|View full text |Cite
|
Sign up to set email alerts
|

Fast Segmentation From Blurred Data in 3D Fluorescence Microscopy

Abstract: We develop a fast algorithm for segmenting 3D images from linear measurements based on the Potts model (or piecewise constant Mumford-Shah model). To that end, we first derive suitable space discretizations of the 3D Potts model, which are capable of dealing with 3D images defined on non-cubic grids. Our discretization allows us to utilize a specific splitting approach, which results in decoupled subproblems of moderate size. The crucial point in the 3D setup is that the number of independent subproblems is so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Staircase artifacts (Knoll et al 2011) have been observed in the reconstruction results of TSD-FISTA. Previous research has shown that incorporating operation directions and utilizing isotropic discretization can lead to improved reconstruction quality in 3D fluorescence microscopy (Storath et al 2017). However, our analysis in appendix E suggests that implementing TSD-FISTA with 13 isotropic-discretization operation directions does not yield significant improvements in MPI reconstruction quality compared to TSD-FISTA with 3 operation directions.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Staircase artifacts (Knoll et al 2011) have been observed in the reconstruction results of TSD-FISTA. Previous research has shown that incorporating operation directions and utilizing isotropic discretization can lead to improved reconstruction quality in 3D fluorescence microscopy (Storath et al 2017). However, our analysis in appendix E suggests that implementing TSD-FISTA with 13 isotropic-discretization operation directions does not yield significant improvements in MPI reconstruction quality compared to TSD-FISTA with 3 operation directions.…”
Section: Discussionmentioning
confidence: 60%
“…The 3 operation directions in ( 21) can be extended to 13 operation directions for almost isotropic discretization (Storath et al 2016(Storath et al , 2017)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The piecewise-constant assumption holds in many CT imaging problems such as industrial inspection [33], [34] or assessment of bone microstructure in medicine [35], [36]. Many different priors are possible for such volumes, such as minimum L 0norm [13], [37], sparse Haar transform [16], or Gauss-Markov-Potts prior [14].…”
Section: Combination With Gauss-markov-potts Prior Model On the Vmentioning
confidence: 99%
“…Moreover, Gauss-Markov-Potts prior allows variability in the classes thanks to the introduction of variances v. Another Potts model, which promotes minimum L 0 -norm for the gradient of the volume, is used in [13] for CT. The reconstruction algorithm in [13] is an instance of ADMM [42], and performs a variable-splitting in each direction used to compute the gradient : as a result, it requires more memory than the reconstruction algorithm proposed in [14], and has been only applied to small volumes in 3D [37].…”
Section: Combination With Gauss-markov-potts Prior Model On the Vmentioning
confidence: 99%
“…Finding u given g as in ( 1) is an ill-posed (under-determined) inverse problem whose solution requires the use of suitable regularization. In a variety of works [12,13,11,4], Storath et al considered the inverse Potts regularization model for joint image restoration and segmentation. Heuristically, such approach is based on the use of a penalized regularization functional defined in terms of an 0type gradient smoothing prior reducing noise and preserving distinctive details (such as image edges).…”
Section: Introductionmentioning
confidence: 99%